FEATURES OF ANXIETY AND DEPRESSION IN WOMEN - Makhamatjanova, N.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
This article is aimed at studying the specific features of anxiety and depression in women. The goal is to deepen understanding of the complex mechanisms of these diseases by studying the interaction of biological, psychological, and social factors, as well as to help develop effective diagnostic and treatment strategies. The study analyzes such factors as traumatic experiences, stress levels, low self-esteem, hormonal changes, lack of social support, and socio-economic difficulties. The results show the interaction and significance of these factors in the development of anxiety and depression in women. The study provides data for the creation of individual approaches to the diagnosis and treatment of anxiety and depression in women.